Fatores associados ao risco de suicídio em pós-graduandos - Abreu, Evelyn Kelly das Neves (2020)
Introduction: Suicide is a multifactorial phenomenon, still little explored in the population of graduate students. The same can be associated with socioeconomic and demographic, academic and health factors in stricto sensu graduate students. Objective: to analyze the factors associated with suicide risk in graduate students. Method: cross-sectional analytical study, developed at a federal university in the Midwest of Brazil, with 565 stricto sensu graduate students, from August to November 2019. Instruments used in data collection: questionnaire with demographic, socioeconomic, academic and of health; Mini International Neuropsychiatric Interview (MINI), used in an adapted way to assess the risk of current suicide; CAGE questionnaire, acronym for the questions - Cut down, Annoyed by criticism, Guilty and Eye-opener, used to identify alcohol abuse; Depression, anxiety and stress scale (DASS 21) and Epworth Sleepiness Scale (ESE), to check for the presence of excessive daytime sleepiness. Pearson's chi-square test was used for bivariate analysis, and Poisson regression for multiple analysis. Research approved by the Health Research Ethics Committee, No. 3,462,827. Results: presented in manuscript form. The prevalence of suicide risk was 40.18%. Regarding demographic and socioeconomic variables, they were characterized as: median age of 30 years, heterosexual (85,13%), with faith practice (79,11%), concerned with the financial situation (72,92%), female ( 67,96%), with a partner (51,68%), whites (45,66%), who moved to another city to graduate (39,82%) and lived alone (19,47%). The following percentages were observed for academic variables: master's students (65,84%), doctoral students (34,16%), without a scholarship (52,92%), activity parallel to graduate studies (52,21%) , loss of research due to lack of funding (43,36%), physical structure of the course that did not meet the needs (30,44%). They reported a family relationship impaired by the demands of graduate studies (20,00%), poor relationship with course technicians (13,98%), colleagues (11,86%), mentor (10,44%) and teachers (10,09%). They did not find the disciplines and activities offered by the course important for research (33,27% and 32,21% respectively), did not perceive the meetings with productive advisors (17,35%) and did not find the academic work significant and inspiring (12,04%). There was evidence of pressure for publication (50,44%), not being optimistic about future professional perspectives (45,31%), difficulties in writing (36,11%), prejudice in the research due to procedures by the Ethics Committee (28,32%), impediment to perform leisure activities due to the demands of the graduate (24,96%) and disagreement as to the conclusion of the graduate in the regular time (20,71%). Graduate students who suffered discrimination in the course were 10,09% and did not feel welcomed to report such a situation 73,45%. Health variables: presence of symptoms of anxiety (54,34%), depression (52,04%), stress (50,27%), excessive daytime sleepiness (46,73%), who used psychiatric drugs during graduate students with or without medical prescription (35,58%), who did not seek a health service when needed during the course (30,09%), with current use of psychotropic drugs and illicit drugs during their lives (25,84% ) and alcohol abuse (10,09%). It was identified that the variables symptoms of depression and anxiety (p <0,001), use of psychotropic drugs during graduate school (p <0,001), not having a significant and inspiring academic work (p = 0,013), faith practice (p = 0,015), age> 30 years (p = 0,029), poor relationship with colleagues in the graduate program (p = 0,033), family relationship impaired by the demands of the graduate program (p = 0,036) and concern about the financial situation (p = 0,048), were associated with the current suicide risk dependent variable. The stricto sensu enrolled course variable remained in the final model only as an adjustment variable for this model. Conclusion: the associated factors comprised the socioeconomic, academic and health variables. The findings reinforce the need to expand the discussion on the theme in the postgraduate environment, as well as the importance of developing policies and programs aimed at graduate students, contributing to reduce the risks of suicide and its prevention.